The EMT-activator ZEB1 induces bone metastasis associated genes including BMP-inhibitors - Mock, Kerstin; Preca, Bogdan-Tiberius; Brummer, Tilman; Brabletz, Simone; Stemmler, Marc; Brabletz, Thomas (Oncotarget, 2015)
Tumor cell invasion, dissemination and metastasis is triggered by an aberrant activation of epithelial-to-mesenchymal transition (EMT), often mediated by the transcription factor ZEB1. Disseminating tumor cells must acquire specific features that allow them to colonize at different organ sites. Here we identify a set of genes that is highly expressed in breast cancer bone metastasis and activated by ZEB1. This gene set includes various secreted factors, e.g. the BMP-inhibitor FST, that are described to reorganize the bone microenvironment. By inactivating BMP-signaling, BMP-inhibitors are well-known to induce osteolysis in development and disease. We here demonstrate that the expression of ZEB1 and BMP-inhibitors is correlated with bone metastasis, but not with brain or lung metastasis of breast cancer patients. In addition, we show that this correlated expression pattern is causally linked, as ZEB1 induces the expression of the BMP-inhibitors NOG, FST and CHRDL1 both by directly increasing their gene transcription, as well as by indirectly suppressing their reduction via miR-200 family members. Consequently, ZEB1 stimulates BMP-inhibitor mediated osteoclast differentiation. These findings suggest that ZEB1 is not only driving EMT, but also contributes to the formation of osteolytic bone metastases in breast cancer.
EVALuna2:10197